Longitudinal relationship between intramuscular adipose tissue of the quadriceps and activities of daily living in older inpatients. Issue 6 (26th October 2021) - Akazawa, Naoki; Kishi, Masaki; Hino, Toshikazu; Tsuji, Ryota; Tamura, Kimiyuki; Hioka, Akemi; Moriyama, Hideki
Abstract: Background: The longitudinal relationship between intramuscular adipose tissue of the quadriceps and activities of daily living (ADL) in older inpatients remains unclear. This study aimed to examine whether decrease of intramuscular adipose tissue of the quadriceps in older inpatients is related to the recovery of ADL than increase of muscle mass. Methods: This longitudinal study included 202 inpatients aged ≥65 years [median age: 83.0 (77.0–88.0), 56.4% female]. Recovery of ADL during hospital stay was assessed using the change in Barthel index (BI) score (i.e. BI score at discharge minus BI score at admission) and BI score at discharge. Intramuscular adipose tissue and muscle mass of the quadriceps were assessed using echo intensity and muscle thickness on ultrasound images, respectively. Higher echo intensity indicates greater intramuscular adipose tissue. Multiple regression analysis was performed to identify the factors independently associated with the change in BI score and BI score at discharge. Changes in quadriceps echo intensity and thickness and subcutaneous fat thickness of the thigh, quadriceps echo intensity and thickness, and subcutaneous fat thickness of the thigh at admission, age, sex, days from onset disease, BI score at admission, and disease were set as independent variables. Results: The means of the change in quadriceps echo intensity and thickness were −2.3 ± 15.7 and 0.1 ± 0.4 cm, respectively. The median of the change in BI score was 15.0 (0.0–30.0). The quadriceps echo intensity at discharge was significantly lower than at admission ( P = 0.043). The quadriceps thickness ( P = 0.004) and BI score at discharge ( P < 0.001) were significantly higher than those at admission. Change in quadriceps echo intensity was independently and significantly associated with the change in BI score (β = −0.25, P = 0.006) and BI score at discharge (β = −0.18, P = 0.006). In contrast, change in quadriceps thickness was not independently and significantly associated with the change in BI score (β = 0.09, P = 0.244) and BI score at discharge (β = 0.06, P = 0.244). Conclusions: Our study indicates that a decrease of intramuscular adipose tissue of the quadriceps is related to the recovery of ADL than an increase of muscle mass in older inpatients. Intramuscular adipose tissue of the quadriceps in older inpatients is considered to be a predictor for the recovery of ADL, and intervening for intramuscular adipose tissue may be important for improving ADL in older inpatients.